IS ASSIMILATION THEORY DEAD? THE EFFECT OF ASSIMILATION ON ADOLESCENT WELL-BEING - Greenman, Emily (2008)
The relationship between assimilation and the well-being of immigrant children has been the focus of debate in the recent sociological literature. Much of this work has questioned whether classical theories of immigrant adaptation, which assumed assimilation to be an integral part of the process of upward mobility for immigrants, are still applicable to today’s immigrant children. This study reevaluates the applicability of classical assimilation theory with a comprehensive empirical assessment of the relationship between assimilation and the well-being of Hispanic and Asian immigrant adolescents. Using Add Health data, we examine the effect of different aspects of assimilation on educational achievement, psychological well-being, and at-risk behaviors. We find that the effect of assimilation varies greatly depending on the ethnic group and outcome under consideration, but that it is generally related to both greater academic achievement and more at-risk behavior. We conclude that assimilation theory is still relevant, but suggest an interpretation that emphasizes a process of decreasing differences between groups rather than either detrimental or beneficial effects of assimilation.